A CTCF-Binding Element and Histone Deacetylation Cooperatively Maintain Chromatin Loops, Linking to Long-Range Gene Regulation in Cancer Genomes - Tang, Ran; Li, Yiqun; Han, Fang; Li, Zhenzhi; Lin, Xiaoyu; Sun, Haoxiu; Zhang, Xiaoqing; Jiang, Qinghua; Nie, Huan; Li, Yu (Frontiers in Oncology, 2022)
Background： Genes spanning long chromosomal domains are coordinately regulated in human genome, which contribute to global gene dysregulation and carcinogenesis in cancer. It has been noticed that epigenetic modification and chromatin architecture may participated in the regulation process. However, the regulation patterns and functional elements of long-range gene regulation are unclear. Methods: Based on the clinical transcriptome data from different tumor sets, a novel expressional correlation analysis pipeline was performed to classify the co-regulated regions and subsets of inter-correlated regions. GLAM2 program was used to predict conserved DNA elements that enriched in regions. Two conserved elements were selected to delete in Ishikawa and HeLa cells by CRISPR-Cas9. SAHA treatment and HDAC knock-down were used to change the histone acetylation status. Using qPCR, MTT and scratch healing assay, we evaluate the effect on gene expression and cancer cell phenotype. By DNA pull-down and ChIP, the element binding proteins were testified. 3C and 3D-FISH were performed to depict the alteration in chromatin architecture. Results: In multiple cancer genomes, we classified subsets of coordinately regulated regions (sub-CRRs) that possibly shared same regulatory mechanisms and exhibited similar expression patterns. A new conserved DNA element (CRE30) was enriched in sub-CRRs and associated with cancer patient survival. CRE30 could restrict gene regulation in sub-CRRs and affect cancer cell phenotypes. DNA pull-down showed multiple proteins including CTCF were recruited on CRE30 locus, and ChIP assay confirmed the CTCF binding signals. Subsequent results uncovered that as an essential element, CRE30 maintained chromatin loops and mediated compact chromatin architecture. Moreover, we found that blocking global histone deacetylation induced chromatin loop disruption and CTCF dropping in the region containing CRE30, linked to promoted gene regulation. Additionally, similar effects were observed with CRE30 deletion in another loci of chromosome 8. Conclusions: Our research clarified a new functional element that recruits CTCF and collaborates with histone deacetylation to maintain high order chromatin organizations, linking to long-range gene regulation in cancer genomes. The findings highlight close relationship among conserved DNA element, epigenetic modification and chromatin architecture in long-range gene regulation process.